2019
DOI: 10.1016/j.idcr.2019.e00578
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian abscess caused by Helicobacter cinaedi in a patient with endometriosis

Abstract: Helicobacter cinaedi is a rarely encountered pathogen that easily induces bacteremia. Various foci of H. cinaedi infection have been reported; however, no case of adnexal abscess caused by H. cinaedi has been reported in the English literature. We herein report a case of ovarian abscess caused by H. cinaedi . A 38-year-old nulligravid Japanese woman was admitted to our hospital with an adnexal abscess. Clinical findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Helicobacter cinaedi was isolated from cultures of blood and ovarian abscess fluid after oophorectomy. Eradication of H. cinaedi was performed successfully with intravenous ampicillin/sulbactam for 2 weeks, followed by oral amoxicillin for an additional 2 weeks 7 . Multilocus sequence typing (MLST) and antimicrobial susceptibility testing (AST) of H. cinaedi were evaluated among 16 successive H. cinaedi blood clinical isolates.…”
Section: Presence Of Non‐helicobacter Pylori Helicobacter Species In mentioning
confidence: 99%
“…Helicobacter cinaedi was isolated from cultures of blood and ovarian abscess fluid after oophorectomy. Eradication of H. cinaedi was performed successfully with intravenous ampicillin/sulbactam for 2 weeks, followed by oral amoxicillin for an additional 2 weeks 7 . Multilocus sequence typing (MLST) and antimicrobial susceptibility testing (AST) of H. cinaedi were evaluated among 16 successive H. cinaedi blood clinical isolates.…”
Section: Presence Of Non‐helicobacter Pylori Helicobacter Species In mentioning
confidence: 99%
“…To date, H. cinaedi is a poorly studied pathogen, but more and more human diseases associated with this bacterium are documented each year ( van der Ven et al, 1996 ; Lewis et al, 2007 ; Nishida et al, 2016 ). One of the known H. cinaedi -associated diseases is bacteremia ( Fox-Lewis et al, 2020 ; Fujita et al, 2021 ), but other pathologies such as cellulitis ( Lenskaya et al, 2022 ), ovarian abscess ( Sato et al, 2019 ), and vertebral osteomyelitis ( Hase et al, 2018 ) are also reported. Among patients with H. cinaedi -associated pathologies, there are different age groups, including young people without immunodeficiencies.…”
Section: Introductionmentioning
confidence: 99%